Optical interrogation of sympathetic neuronal effects on macroscopic cardiomyocyte network dynamics - Burton, R-A; Tomek, J; Ambrosi, CM; Et al. (Elsevier (Cell Press), 2020)
Cardiac stimulation via sympathetic neurons can potentially trigger arrhythmias. We present approaches to study neuron-cardiomyocyte interactions involving optogenetic selective probing and all-optical electrophysiology to measure activity in an automated fashion. Here we demonstrate the utility of optical interrogation of sympathetic neurons and their effects on macroscopic cardiomyocyte network dynamics to address research targets such as the effects of adrenergic stimulation via the release of neurotransmitters, the effect of neuronal numbers on cardiac behavior, and the applicability of optogenetics in mechanistic in vitro studies. As arrhythmias are emergent behaviors that involve the coordinated activity of millions of cells, we image at macroscopic scales to capture complex dynamics. We show that neurons can both decrease and increase wave stability and re-entrant activity in culture depending on their induced activity—a finding that may help us understand the often conflicting results seen in experimental and clinical studies.